2013
DOI: 10.1603/ec12378
|View full text |Cite
|
Sign up to set email alerts
|

No Sex-Related Differences in Mortality in Bed Bugs (Hemiptera: Cimicidae) Exposed to Deltamethrin, and Surviving Bed Bugs Can Recover

Abstract: Exposure of a pyrethroid-susceptible strain of bed bugs, Cimex lectularius L. (Hemiptera: Cimicidae) to varying concentrations of deltamethrin for 24 h indicated no significant difference in mortality between males, females, and nymphs at 24 nor at 168 h postexposure when bed bugs were removed to untreated surfaces at 24 h. In addition, many bed bugs classified as morbid or moribund at 24 h and removed to untreated surfaces at this time, recovered by 336 h (2 wk) and were capable of feeding when given the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…at day 1) or starved for up to 9 days [ 56 ]. This aligns with the practices of other laboratories employing bed bugs in insecticide-based bioassays, with most selectively using male bed bugs, aging between 7–10 days after emergence, and not feeding for 5–8 days prior to the experiment(s), if at all [ 6 , 11 , 13 , 57 59 ].…”
Section: Discussionsupporting
confidence: 56%
“…at day 1) or starved for up to 9 days [ 56 ]. This aligns with the practices of other laboratories employing bed bugs in insecticide-based bioassays, with most selectively using male bed bugs, aging between 7–10 days after emergence, and not feeding for 5–8 days prior to the experiment(s), if at all [ 6 , 11 , 13 , 57 59 ].…”
Section: Discussionsupporting
confidence: 56%
“…We evaluated only adult males, while the previous studies on mosquitoes were forced to evaluate only females because they are the only life stage that consumes a blood meal [ 24 , 25 ]. Feldlaufer et al [ 12 ] reported no difference in the toxicity of insecticides between males and females, however they only measured the effects of continuous exposure. In addition, Choe and Campbell [ 16 ] found a significant difference in the tolerance of 1 d and 9 d starved bed bugs when continually exposed to dried residues of deltamethrin, but no differences at these times when topically applied.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization has standards for mosquito testing (non-blood fed, 3–5 d post emergence), however no such standard exist for bed bugs [ 32 ]. Numerous studies have tested bed bugs at various times post feeding, ranging from 5 d to >12 d [ 11 , 12 , 13 ]. Difference in feeding status among tests may confound our understanding of the effects of various insecticides, which is critical as we continue to search for the most effective management strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations